2006
DOI: 10.1523/jneurosci.2801-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α Mediates Oligodendrocyte Death and Delayed Retinal Ganglion Cell Loss in a Mouse Model of Glaucoma

Abstract: Glaucoma is a widespread ocular disease characterized by a progressive loss of retinal ganglion cells (RGCs). Previous studies suggest that the cytokine tumor necrosis factor-␣ (TNF-␣) may contribute to the disease process, although its role in vivo and its mechanism of action are unclear. To investigate pathophysiological mechanisms in glaucoma, we induced ocular hypertension (OH) in mice by angle closure via laser irradiation. This treatment resulted in a rapid upregulation of TNF-␣, followed sequentially by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
362
1
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 398 publications
(383 citation statements)
references
References 57 publications
15
362
1
5
Order By: Relevance
“…A candidate proapoptotic factor downstream of p75 NTR is tumor necrosis factor alpha (TNFα) because exogenous and endogenous TNFα can induce death of retinal neurons (17)(18)(19) and because p75 NTR activates NF-κB, a transcription complex that is a potent inducer of TNFα production (20)(21)(22). To address whether TNFα could play a role in proNGF-induced RGC killing, we first determined if retinal TNFα levels were increased in eyes injected with proNGF.…”
Section: Resultsmentioning
confidence: 99%
“…A candidate proapoptotic factor downstream of p75 NTR is tumor necrosis factor alpha (TNFα) because exogenous and endogenous TNFα can induce death of retinal neurons (17)(18)(19) and because p75 NTR activates NF-κB, a transcription complex that is a potent inducer of TNFα production (20)(21)(22). To address whether TNFα could play a role in proNGF-induced RGC killing, we first determined if retinal TNFα levels were increased in eyes injected with proNGF.…”
Section: Resultsmentioning
confidence: 99%
“…An important hypothesis in glaucoma posits trophic deprivation proximally at the optic nerve head along with loss of axonal integrity (5)(6)(7)(8)43). Myriad somatic and dendritic factors are also likely to contribute, including intrinsic pressure sensitivity and synapse elimination (35,44).…”
Section: Discussionmentioning
confidence: 99%
“…This second process likely involves damage to the axon that results in the rapid degeneration of the distal portion while there is still preservation of the proximal portion of the axon for as long as a month. Separate study of these two degeneration processes in DBA/2J and other promising mouse models of glaucoma (Mabuchi et al, 2003;Nakazawa et al, 2006;Senatorov et al, 2006) especially after various treatments that have been reported to slow disease progression in DBA/2J mice (Anderson et al, 2005;Ward et al, 2007;Zhong et al, 2007) will likely lead to both a better understanding of disease mechanisms as well as the discovery of additional promising interventions.…”
Section: Discussionmentioning
confidence: 99%